Design Of Pavement Using Buton Natural Rock Asphalt Stabilized Subgrade Soil - Lely Rizkiyawati; Wilujeng Ashri Nastiti; Gatot Rusbintardjo; Prabowo Setiyawan (International Conference on Coastal and Delta Areas, 2017)
The performance of pavements is governed by the strength of the subgrade, because subgrade is roadbed soil where the pavement structure is laid. If bearing capacity of the subgrade high, deformation of pavement will not occur and it is not easy to deteriorate. In the contrary, if bearing capacity of the subgrade low, pavement deformation will occur and pavement will deteriorate. This research have objectives to analysis the pavement structure of using existing subgrade soil and using subgrade stabilized with Buton Natural Rock Asphalt (BNRA).  The road connecting Semarang - Purwodadi where always in worst condition was used for study in this research. Semarang – Purwodadi road is laid over montmorillonite expansive clay with lower bearing capacity or have low CBR value only 1 to 2 %. To analysis the pavement structure, both flexible and rigid pavement, AASHTO 1993 pavement design are used. The result show that flexible pavement structure laid over stabilized soil have thinner pavement structure compare to the one laid over the subgrade of original expansive clay soil. Similarly for rigid pavement, the thick of concrete slab over the subgrade of expansive clay is 30 cm, and if laid over the subgrade of stabilized expansive clay with Buton Natural Rock Asphalt (BNRA) is only 25cm. It can be concluded that Buton Natural Rock Asphalt (BNRA), have significant influence to the strength and bearing capacity of expansive clay soil.  Keywords: asbuton, stabilized subgrade, expansive clay soil, AASHTO